Citizen science enables a new locality record for a critically endangered toad, Peltophryne Florentinoi Moreno & Rivalta, 2007 - Díaz, Luis M.; Lemm, Jeffrey M.; Briggs, Erick M.; Clark, Sharon; Dannenberg, Andrew L.; Gamber, Russell G.; Kelly, Jane; Laughlin, Patrick; Markowski, Gary; Shelley, Erin L.; Van Bakel, Adrian B. (Novitates Caribaea, 2019)
The Zapata Toad (Peltophryne florentinoi) is reported from a new locality, Guajimico, which extends the distribution of this species to the Cienfuegos Province, in the central region of Cuba.